Optimising high intensity treadmill training using vVO2max and Tmax - Smith, T. P.; Dilger, J.; Coombes, J. S. (2001)
High intensity treadmill training has been reported to improve performance in middle distance athletes. Two parameters used to prescribe treadmill training programs are vVO2max, (running velocity at VO2max) and Tmax (time an athlete can sustain their vVO2max). However few studies have attempted to determine the optimum use of these parameters. The purpose of this study was to investigate the effectiveness of interval training using either 60% or 70% Tmax as exercise duration, while interval intensity is set at 100% vVO2max. Twenty-six highly trained middle distance athletes volunteered to participate in the study, they were randomised to either a control, 60% or 70% Tmax training group. Prior to a four week training program, subjects completed a 3000m Time Trial (TT), 5000mTT, and three each of VO2max, vVO2max and Tmax tests. Subjects in the 60 and 70% Tmax groups undertook two treadmill interval sessions per week at 100% vVO2max and their respective Tmax duration. These sessions were separated by a 30 minute recovery run at 60% vVO2max. Subjects in the control group continued their regular training. The 60% Tmax group significantly improved (p<0.05) their 3000m TT by 17.5 sec, while the 70% Tmax and control groups had no significant TT improvements. Furthermore subjects in the 60% Tmax group significantly improved (p<0.001) Tmax (219 pre vs 268 sec post training) while vVO2max improved (19.1 pre vs 20.1 k/hr post training). The 70% group and control group had no significant improvement in Tmax or vVO2max. Blood lactate was significantly lower (p<0.05) in the 60% Tmax group when comparing values from the first and last training session, (9.64 vs 8.74 mmol). Findings indicate that in middle distance athletes high intensity treadmill training using intervals at 100% vVO2max and 60% Tmax duration significantly improves performance.